PENGARUH LAMA PENGGUNAAN MULSA DAN DOSIS PUPUK KANDANG TERHADAP PERTUMBUHAN CABAI (Capsilum Annum) SEBAGAI BAHAN PENYUSUN PETUNJUK PRAKTIKUM BIOLOGI KELAS XII SMA NEGERI 1 BARAT - Zainal Aripin (Florea : Jurnal Biologi dan Pembelajarannya, 2016)
Learning biology is one area of Natural Sciences (IPA) which is integral with practical  activities. The lab activities are very important in understanding science concepts. One material that requires practical learning activities more meaningful so that the material of plant growth and development of class XII Science. It would require new innovation in the development lab manual. This study aims to make research the effect of duration of use and dose of manure mulchon plant growth chili as the building blocks lab manual.This research was conducted using a "Research and Development" (Research and Development). At this stage of research using Grid Design Divided (RPT) which uses two treatments, use of mulch and manure dose use with penggulangan 3 times, while in the Development stage using the results of research into practical instructions were validated by various experts. Based on the results of research and development,we can conclude several things: study the effect of long use of mulch and a dose of manure on the growth of chili can be used as the building blocks of manual lab work with Highlights Growth and Development Plant class XII Science developed in this study expressed very valid, based validation results from two experts namely materials experts and media specialists, with a 88% value validation.